Development of a Dual Frequency Microwave Moisture Sensor System Based Circular Microstrip Antenna - Ghretli, Mohamed Mustafa (2005)
A dual frequency microwave moisture sensor based on far field reflection technique using two circular microstrip antenna pairs was developed and used to measure moisture content of various lossy liquid solutions. The sensor used two dielectric resonator oscillators as microwave sources in the X-band with oscillating frequencies of 8.48 and 10.69 GHz. Two wideband coaxial detectors were used to measure the amplitude of the reflected signals. Theoretical calculation based on quasi-static cavity model with infinite ground plane approximation for circular microstrip antenna was carried out to evaluate design parameters such as antenna radius at resonance, efficiency, gain, bandwidth, feed point location ... etc. To this end a Visual Basic program was written and documented to evaluate all the design parameters needed Antennas edge separation distances and E-plane configurations were considered carefully to reduce mutual coupling between elements. The final layout was printed on a single dielectric substrate. Radiation characteristics of the antennas, Sparameters and input impedances at resonance were measured using vector network analyzer and they compared satisfactory to theoretical simulations. The optimum thickness of the sample holder and the air gap between the antennas and the sample holder were evaluated experimentally to ensure maximum signals at the detectors. Good agreements to theoretical expected values were found. The analysis of the complex electromagnetic waves in this reflected-type system is presented using signal flow graphs and solved by Mason's non-touching loops rules. The whole sensor system was interfaced to a personal computer through data acquisition card. This automated the calibration procedures and facilitated the switching time between the sources. Graphical user interface panel was written in LabView language to guide the user through calibration measurements and. As an application example, the whole system was tested using diluted rubber latex with moisture content ranging from 39.8 to 95.2% wet basis. The sensor has predicted moisture contents with standard error of performance of *O.49% moisture content using weighted average calibration method. Moisture contents of latex samples in temperature range of 25 to 63°C were measured successfully with an accuracy off 1.3% MC wet basis compared to standard oven drying method